Structure Matters: Mentored Research Experiences and Their Impact on Black Students in STEM. - Johnson, Kawana (Experiential Learning and Teaching in Higher Education, 2025)
The author uses qualitative methods to examine a mentored research experience at a national lab in the United States and its impact on Black students in STEM. An analysis of the data revealed that participation increased their interest in pursuing a career in STEM, expanded their professional network, and enhanced their skills. Despite the lack of mentors with the same demographic background, participants described the experience and environment as positive exposing them to new cultures and knowledge. Overall, findings highlight the important role that structured mentoring experiences play in the development of future STEM professionals of color.